Distribution of Residual Stresses in Polymer Reinforced Carbon Nanotubes and Laminated Carbon Fibers - Ahmad Reza Ghasemi; Mohammad Mohammadi-Fesharaki (Mechanics of Advanced Composite Structures)
In this study, the distribution of residual stress in fiber-reinforced nanocomposites is investigated. Fiber-reinforced nanocomposite is composed of three substances: carbon fiber, carbon nanotube (CNT), and polymer matrix. Unit cells in hexagonal packing array with different arrays as unit cell, 3*3 and 5*5 arrays have been selected as suitable for finite element analysis of residual stresses. Radial and tangential residual stress have been determined in different directions by finite element analysis using ABAQUS commercial software for each phase individually. The effect of the CNTs’ various volume fractions (0%, 1%, 2%, and 3%) on residual stress distribution has been studied in different directions and compared to one another for each phase. Results show that the 3*3 unit cells arrays are suitable for modeling micro-residual stresses, and the results of this array are reliable. In addition, adding a 3% volume fraction of CNTs to the matrix is the best option for reduction of overall residual stresses with minimal fluctuation in local micro-residual stresses.